Insights into the microbiome of mine drainage from the Mária mine in Rožňava, Slovakia: a metagenomic approach - Hagarová, Lenka; Kupka, Daniel (Frontiers in Microbiology, 2025)
The Mária mine, particularly the Strieborná vein, in Rožňava, is one of the most important mines in Slovakia, containing Ag-bearing tetrahedrite (40–46 wt% Cu, 26 wt% Sb, ~1 wt% Ag), making it an important source of strategic and critical raw materials. This mine discharges a unique neutral-pH (6.9), metal-rich mine water drainage (402 mg L−1 SO42−, 4.65 mg L−1 Fe) that has remained microbiologically uncharacterized. This study presents the first comprehensive shotgun metagenomic survey of this mine effluent, generating ~227 million high-quality reads that assembled into 157,676 contigs and 378,023 non-redundant genes. Taxonomic analysis revealed a community dominated by Betaproteobacteria (> 66%), with abundant lithotrophic genera Sulfuritalea (6.93%), Ferrigenium (5.45%), Gallionella (3.79%), and Sideroxydans (3.65%), alongside the heterotrophic genus Pseudomonas (5.2%). Among the most prevalent neutrophilic iron-oxidizing bacterial strains were Sulfuritalea hydrogenivorans (6.93%), Ferrigenium kumadai (5.45%) and Gallionella capsiferriformas (3.79%). Acidophilic genera (e.g., Thiobacillus sp. at 0.43%, Ferrovum myxofaciens, Acidithiobacillus ferrivorans, Leptospirillum ferrooxidans) collectively accounted for <1% of the community. Functional annotation against KEGG, CAZy, COG, eggNOG, Swiss-Prot, CARD and BacMet databases demonstrated pronounced enrichment of iron cycling (e.g., the iron complex outer-membrane receptor protein TC.FEV.OM), sulfur oxidation (e.g., SoxA, SoxX, SoxB), carbon turnover (glycosyltransferase and glycoside hydrolase families) and nitrogen cycling (e.g., NifH, NifD, NirK, glnA). The antibiotic-resistance profile was dominated (> 95%) by tetracycline and fluoroquinolone determinants, while metal-resistance systems for Ni, Ag, As, Cu and Zn (including CzcD, CzcA, CznA, ArsD and AioX/AoxX) were likewise pervasive. This integrated taxonomic-functional portrait highlights a microbiome finely adapted to this unique geochemistry, combining lithotrophic metabolisms with multi-metal resistance. Our findings establish a critical baseline for long-term monitoring and highlight a high abundance of neutrophilic Fe(II)-oxidizers, suggesting they may represent promising candidates for targeted cultivation and subsequent evaluation in biotechnology applications.